A whole-exome sequencing study of patent foramen ovale: investigating genetic variants and their association with cardiovascular disorders - Li, Xinyi; Xie, Lingling; Dai, Jin; Zhou, Xinbin; Chen, Tingting; Mao, Wei (Frontiers in Genetics, 2024)
Background: Patent foramen ovale (PFO) has a genetic predisposition and is closely associated with cryptogenic stroke (CS), migraine, decompression sickness, and hypoxemia. Identifying PFO-related mutant genes through whole-exome sequencing (WES) can help in the early recognition of cardiovascular genetic risk factors, guide timely clinical intervention, and reduce the occurrence of cardiovascular events.We analyzed mutant genes from ClinVar and OMIM databases. WES was performed on 25 PFO patients from Zhejiang Provincial Hospital of Chinese Medicine. Pathogenicity of variants was evaluated using American College of Medical Genetics and Genomics (ACMG) and Association for Molecular Pathology (AMP) guidelines.In ClinVar (Feb 4th, 2023), 113 coding gene mutations were found, including 83 associated with PFO.From OMIM (Apr 18th, 2023), 184 gene mutations were analyzed, with 110 mutant coding genes. WES identified pathogenic mutations in 2 of 25 PFO patients (8%). LDLR, SDHC, and NKX2-5 genes were linked to PFO and primarily involved in myocardial tissue function. NKX2-5 may play a crucial role in PFO development, interacting with NOTCH1, GATA4, MYH6, SCN5A signaling pathways regulating cardiomyocyte characteristics.We identified pathogenic mutations in LDLR, SDHC, and NKX2-5 genes, implying their role in PFO development. Functional enrichment analysis revealed NKX2-5's interaction with signaling pathways regulating cardiomyocyte function. These findings enhance our understanding of PFO's genetic basis, suggesting potential therapeutic targets for future research.